2017
DOI: 10.1038/srep40047
|View full text |Cite
|
Sign up to set email alerts
|

Labeling and in vivo visualization of transplanted adipose tissue-derived stem cells with safe cadmium-free aqueous ZnS coating of ZnS-AgInS2 nanoparticles

Abstract: The facile synthesis of ZnS-AgInS2 (ZAIS) as cadmium-free QDs and their application, mainly in solar cells, has been reported by our groups. In the present study, we investigated the safety and the usefulness for labeling and in vivo imaging of a newly synthesized aqueous ZnS-coated ZAIS (ZnS-ZAIS) carboxylated nanoparticles (ZZC) to stem cells. ZZC shows the strong fluorescence in aqueous solutions such as PBS and cell culture medium, and a complex of ZZC and octa-arginine (R8) peptides (R8-ZZC) can achieve t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 33 publications
0
21
1
Order By: Relevance
“…Cd-based binary nanoparticles have often been used to this end, but we reported the utility of ZAIS particles with visible light emission as a Cd-free probe for cell imaging. 67,68 ZAIS nanoparticles incorporated into living cells enabled clear PL imaging with much less cytotoxicity than that observed for conventional Cd-based binary nanoparticles due to the absence of released Cd 2+ ions. 67 On the other hand, it is well known that near-IR light is more efficiently transmitted through biological tissues than is light in the ultraviolet, visible, or IR wavelength region.…”
Section: Application Of Near Ir-emissive Multinary Nanoparticles To Bmentioning
confidence: 97%
“…Cd-based binary nanoparticles have often been used to this end, but we reported the utility of ZAIS particles with visible light emission as a Cd-free probe for cell imaging. 67,68 ZAIS nanoparticles incorporated into living cells enabled clear PL imaging with much less cytotoxicity than that observed for conventional Cd-based binary nanoparticles due to the absence of released Cd 2+ ions. 67 On the other hand, it is well known that near-IR light is more efficiently transmitted through biological tissues than is light in the ultraviolet, visible, or IR wavelength region.…”
Section: Application Of Near Ir-emissive Multinary Nanoparticles To Bmentioning
confidence: 97%
“…As such, the labeled cells can be monitored not only by fluorescence and bioluminescence imaging but also by positron emission tomography (PET), computed tomography (CT), and magnetic resonance (MR) imaging after transplantation [59,60,61,62]. MR imaging is able to detect a small number of transplanted cells in deep tissues [63]. Furthermore, the cell tracking method involves a short reaction time and label cells with high efficacy.…”
Section: Click Chemistry As a Tool For Cell Engineering In Cell Trmentioning
confidence: 99%
“…For example, the ZnS-ZAIS QDs developed in our studies were confirmed to have cytotoxicity against stem cells that was about 100 times lower than that of CdSe/ZnS QDs. 22 Shang et al onfirmed that GQDs could label human neural stem cells (hNSCs). 36 Almost all non-toxic organic dyes can easily label stem cells through the cell membrane due to low molecular weight and size by the addition of these dyes to cell culture medium.…”
Section: Qd Types and Stem Cell Labeling Strategies Using Qdsmentioning
confidence: 99%
“…QDs with a negatively charged surface and R8 peptide were complexed at an optimum concentration ratio for 15 min, and then the solution including QDs and R8 complexes was added to the cell culture medium. After that, QDs were confirmed to be transduced into cells by the endocytosis pathway within at least 24 h. 12,[14][15][16]22 Meanwhile, Liu et al showed the carbon and graphene dots with various surface passivation schemes by organic or biomolecules ( Fig. 2a).…”
Section: Qd Types and Stem Cell Labeling Strategies Using Qdsmentioning
confidence: 99%
See 1 more Smart Citation